Rediscovering Kurdistan's Cultures and Identities The Call of the Cricket (Palgrave Studies in Cultural Heritage and Conflict, 2018)
Rediscovering Kurdistan's Cultures and Identities: The Call of the Cricket offers insight into little-known aspects of the social and cultural activity and changes taking place in different parts of Kurdistan (Turkey, Iraq, Syria and Iran), linking different theoretical approaches within a postcolonial perspective. The first chapter presents the book's approach to postcolonial theory and gives a brief introduction to the historical context of Kurdistan. The second, third and fourth chapters focus on the Kurdish context, examining ethical changes as revealed in Kurdish literary and cinema narratives, the socio-political role of the Kurdish cultural institutions and the practices of countering othering of Kurdish migrants living in Istanbul. The fifth chapter offers an analysis of the nineteenth-century missionary translations of the Bible into the Kurdish language. The sixth chapter examines the formation of Chaldo-Assyrian identity in the context of relations with the Kurds after the overthrow of the Ba'ath regime in 2003. The last chapter investigates the question of the Yezidis' identity, based on Yezidi oral works and statements about their self-identification.